Exclusão extrajudicial de sócios em sociedades limitadas: pressupostos legais e entendimentos das Câmaras especializadas do TJ-SP - Marconi, Marcela Vieira (2023)
This dissertation proposes the analysis of the exclusion of partners in limited liability companies by deliberations, under the aspect of the legal assumptions provided for in article 1,085 of the Civil Code, and the understanding of the Specialized Chambers of Business Law of the Court of Justice of the State of São Paulo in face of annulment and/or suspension lawsuits judged between January 2019 and December 2022. For such purpose, it will first address the main aspects of limited liability companies and the relationships among their partners, highlighting the economic relevance of such corporate type, the legislative history of partial dissolution, the possibility of exclusion of partners as a hypothesis of this kind of dissolution, the differences between the judicial and extrajudicial modality for exclusion of partners, and the specificities inherent to the causes and consequences of the possible judicial invalidation of extrajudicial exclusions. Next, using the doctrinaire and jurisprudential understandings, will be analyzed the material premise for the extrajudicial exclusion of partners, that is the act of undeniable gravity, analyzing the legal provisions in this regard, the characterization of such acts considering the open legal provision and the immensity of the possibilities of corporate conflicts, and the possibility of contractual establishment of the hypotheses. Finally, still based on doctrinal and jurisprudential understandings, the formal assumptions for extrajudicial exclusion and its specificities will be analyzed, one by one, namely, the need for an authorizing contractual provision, the personal and specific summons, and the meeting to be held with respect to the right of defense of the partner whose exclusion is sought. The intention is, in short, an in-depth study of the discussions and specificities inherent to the theme, with emphasis on how they have been resolved by the Specialized Chambers of Business Law of the Court of Justice of the State of São Paulo